DNA‐Mediated Proximity‐Based Assembly Circuit for Actuation of Biochemical Reactions. (6th September 2018) - Oh, Sung Won; Pereira, Adriana; Zhang, Ting; Li, Tianran; Lane, Ariel; Fu, Jinglin
Abstract: Smart nanodevices that integrate molecular recognition and signal production hold great promise for the point‐of‐care (POC) diagnostic applications. Herein, the development of a DNA‐mediated proximity assembly of biochemical reactions, which was capable of sensing various bio‐targets and reporting easy‐to‐read signals is reported. The circuit was composed of a DNA hairpin‐locked catalytic cofactor with inhibited activity. Specific molecular inputs can trigger a conformational switch of the DNA locks through the mechanisms of toehold displacement and aptamer switching, exposing an active cofactor. The subsequent assembly of an enzyme/cofactor pair actuated a reaction to produce colorimetric or fluorescence signals for detecting target molecules. The developed system could be potentially applied to smart biosensing in molecular diagnostics and POC tests. Abstract : DNA direkt detektiert : Ein robustes DNA‐Nanosystem wurde entworfen, das verschiedene biologische Strukturen erkennt und leicht erkennbare Signale liefert. Darin vermittelt ein DNA‐Logikgatter die nähebasierte Aggregation eines Enzym‐Kofaktor‐Systems, das bestimmte Moleküle erkennt und durch katalytische Prozesse Farb‐ oder Fluoreszenzsignale erzeugt.